2002
DOI: 10.1046/j.1461-0248.2002.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

The interaction between predation and competition: a review and synthesis

Abstract: This review discusses the interface between two of the most important types of interactions between species, interspecific competition and predation. Predation has been claimed to increase, decrease, or have little effect on, the strength, impact or importance of interspecific competition. There is confusion about both the meaning of these terms and the likelihood of, and conditions required for, each of these outcomes. In this article we distinguish among three measures of the influence of predation on compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
610
1
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 616 publications
(634 citation statements)
references
References 115 publications
18
610
1
5
Order By: Relevance
“…This is similar to other predator-prey models in ecological theory (Jansen, 1970;Chase et al, 2002). However, the highest PFU count in this study is 4 Â 10 5 , an order of magnitude lower than the lowest gene copy numbers detected by QPCR.…”
Section: Discussionsupporting
confidence: 89%
“…This is similar to other predator-prey models in ecological theory (Jansen, 1970;Chase et al, 2002). However, the highest PFU count in this study is 4 Â 10 5 , an order of magnitude lower than the lowest gene copy numbers detected by QPCR.…”
Section: Discussionsupporting
confidence: 89%
“…Predators modify the productivity -diversity relationship by altering the abundance and stability of competing prey species (Rosenzweig 1971;Chase et al 2002). For example, simple models have shown that superior resource exploiters dominate unproductive environments, whereas resistance to predation is increasingly favoured as productivity increases (Leibold 1996), a hypothesis that has been confirmed using simplified microcosm communities containing a single strain of phage (predator) and bacteria (Bohannan & Lenski 2000).…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, the type of defense costs regarding competitiveness (resource uptake affinity or growth rate) plays an important role for coexistence. Theory already showed that predator‐mediated coexistence crucially depends on the environmental conditions (Chase et al., 2002), for example, the enrichment level (Genkai‐Kato & Yamamura, 1999; Leibold, 1996; Proulx & Mazumder, 1998), the prey switching behavior of the predator (Abrams & Matsuda, 1993; Fryxell & Lundberg, 1994; Murdoch, 1969), the magnitude of the trade‐off between defense and competitiveness (Abrams, 1999; Kasada, Yamamichi, & Yoshida, 2014; Tirok & Gaedke, 2010), and the difference in both the defense level and the competitiveness between the prey types (Becks, Ellner, Jones, & Hairston, 2010; Ehrlich, Becks, & Gaedke, 2017; Jones & Ellner, 2007). However, the role of different defense mechanisms and competition costs in prey communities remains unclear but holds promise to be decisive for their coexistence and the occurring population dynamics.…”
Section: Introductionmentioning
confidence: 99%